Kazuistiky pacientů s marker chromozómy - Kocárek, E; Novotná, D; Maríková, T; Cernáková, I; Losan, F; Balícek, P; Baxová, A; Havlovicová, M; Goetz, P (Casopis lekaru ceskych, 2004)
Small, usually supernumerary chromosomes, denoted as marker chromosomes or markers, can be represented by various phenotypic expression, that depends on their origin and extent. Our article presents results of molecular cytogenetic analysis (FISH) of 34 patients with identified marker chromosome. In 21 cases a marker derived from acrocentric chromosome was identified, in 9 cases markers of gonosomal origin [der(X), der(Y)], and in 4 patients markers of some other chromosomes (5, 17, 18) were proved. The most frequent marker was that originating from chromosome 15 (8 cases). Two patients with different phenotype, markedly influenced by the extent of pseudoizodicentric chromosome 15 are described. In accordance with hitherto presented data, presence of supernumerary copies of the critical region PWACR (it is the partial trisomy, resp. tetrasomy 15q11-q13) in majority of cases brings about serious affection described as syndrome of the inverted duplication of chromosome 15. The most typical symptoms are psychomotoric retardation, hypotony, neurological symptoms and autistic features. The article stresses the importance of FISH method in the prenatal examination of marker chromosomes.
Keywords: hybridizace in situ fluorescenční; kojenec; karyotypizace; mužské pohlaví; Infant; Adult; Karyotyping; fenotyp; In Situ Hybridization, Fluorescence; Infant, Newborn; Phenotype; ženské pohlaví; novorozenec; Humans; Chromosome Aberrations; chromozomální aberace; dospělí; Female; lidé; Male